Tuning the volume of the immune response: strength and persistence of stimulation determine migration and cytokine secretion of dendritic cells - Luft, Thomas; Maraskovsky, Eugene; Schnurr, Max; Knebel, Katja; Kirsch, Michael; Görner, Martin; Skoda, Radek; Ho, Anthony Dick; Nawroth, Peter Paul; Bierhaus, Angelika (Blood, 2004)
Migration to lymph nodes and secretion of cytokines are critical functions of mature dendritic cells (DCs); however, these 2 functions are not necessarily linked. This is the first report showing that quantitative differences in identical signaling pathways determine DC migration and cytokine secretion. Using different polymerized forms of CD40 ligand, we demonstrate that the strength and persistence of CD40 signaling can induce either function. Induction of monocyte-derived DC (MoDC) migration required a weak and transient CD40 signal, whereas strong and persistent CD40 signaling blocked migration and biased toward cytokine secretion. In contrast to MoDCs, CD40 activation of CD1c+ peripheral blood DCs (PBDCs) induced a nonpersistent, intracellular signaling profile resulting in migratory-type DCs unable to secrete interleukin-12p70 (IL-12p70). Extracellular signal-regulated kinase 1/2 (ERK1/2) and p38K activation synergistically mediated cytokine secretion, whereas migration was enhanced by p38K activation but reduced by persistent ERK1/2 activity. This model of signal strength and persistence also applied when stimulating DCs with intact microbes. Thus, a novel concept emerges in which the type of immune response induced by DCs is tuned by the strength and persistence of DC activating signals.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 03.12.2021